Genome‐wide compound heterozygosity analysis highlighted 4 novel susceptibility loci for congenital heart disease in Chinese population. Issue 3 (29th June 2018) - Jiang, T.; Huang, M.; Jiang, T.; Gu, Y.; Wang, Y.; Wu, Y.; Ma, H.; Jin, G.; Dai, J.; Hu, Z.
Abstract : Genome‐wide association studies (GWASs) have achieved great success in deciphering the genetic cause of congenital heart disease (CHD). However, the heritability of CHD remains to be clarified, and numerous genetic factors responsible for occurrence of CHD are yet unclear. In this study, we performed a genome‐wide search for relaxed forms of compound heterozygosity (CH) in association with CHD using our existing GWAS data including 2265 individuals (957 CHD cases and 1308 controls). CollapsABEL was used to iteratively test the association between the CH genotype and the CHD phenotype in a sliding window manner. We highlighted 17 genetic loci showing suggestive CH‐like associations with CHD ( P  < 5 × 10 −8 ), among which 4 genetic loci had expression quantitative trait loci (eQTL) effects in blood ( P eQTL  < 0.01). After conditional association analysis, each loci had only 1 independently effective signal reaching the significance threshold (rs2071477/rs3129299 at 6p21.32, P  = 2.47 × 10 −10 ; rs10773097/rs2880921 at 12q24.31, P  = 3.30 × 10 −8 ; rs73032040/rs7259476 at 19q13.11, P  = 1.14 × 10 −8 ; rs10416386/rs4239517 at 19q13.31, P  = 1.15 × 10 −9 ), together explained 7.83% of the CHD variance. Among these 4 associated loci, outstanding candidates for CHD‐associated genes included UBC, CFM2, ZNF302, LYPD3 and CADM4 . Although replication studies with larger sample size are warranted, the first CH GWAS of CHD may extend our current knowledge of the genetic contributions to CHD in the Han Chinese population. Abstract :